Comparison of Damage Processes in two Austenitic Steels Under Thermal Cycling and Creep Conditions - Korusiewicz, L.; Krajczyk, A.; Rechul, Z.; Żuchowski, R. (Engineering Transactions, 1993)
Processes of thermal cycling in materials are difficult to analyse because of complexity of the phenomena involved. The aim of the paper was to check the assumption that there is some similarity in failure mechanisms occurring under thermal cycling and stationary creep conditions. To this end deformation processes up to failure were analysed in various austenitic steels. The experiments were carried out on axially loaded cylindrical specimens made of austenitic steels. The specimens were tested in isothermal creep at temperatures 1173, 1123, 1073, 1023K and under thermal cycling conditions over the range 573-1173 K using three different thermal cycles: a saw-toothed and two trapezoidal ones. The investigation was aimed at assessing the contributions of creep and cyclic deformation to failure processes induced by various modes of thermal loading. The Monkman-Grant failure criterion was used to give a relationship between time to failure and steady deformation rate.